2014
DOI: 10.1590/1519-6984.20412
|View full text |Cite
|
Sign up to set email alerts
|

Sampling a biodiversity hotspot: the orchid-bee fauna (Hymenoptera: Apidae) of Tarapoto, northeastern Peru, the richest and most diverse site of the Neotropics

Abstract: The orchid-bee fauna of the region of Tarapoto, northeastern Peru, was surveyed using seventeen different scents as baits to attract orchid-bee males. Six hundred and fifty-nine males belonging to 41 species were actively collected with insect nets during 120 hours in late July and early August, 2012. Euglossa dressleri Moure, 1968, Euglossa laurensi Bembé, 2008, and Euglossa maculilabris Moure, 1968, three species belonging to the Euglossa cybelia species-group, are here reported for Peru for the first time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
0
14
1
Order By: Relevance
“…Roubik (2004a) had already suggested that surveys of orchid-bee males with scent baits during a single day have great utility, and may reveal almost as much about local community structure as studies lasting a full year. The protocol proposed by Nemésio (2010b) has already been used in more than twenty areas in northeastern Brazil (Nemésio, 2010b; this study), southern Bahia (Nemésio, 2011a(Nemésio, , 2013a, northern Espírito Santo (Nemésio, 2011b(Nemésio, , 2013b, Minas Gerais (Nemésio, 2012c;Nemésio and Paula, 2013), and the Peruvian Amazon (Nemésio et al, 2014), always with a high number of collected specimens during a relatively short period of time. With more than 3,000 bees collected in only ten days, the present study revealed one of the highest abundances ever recorded with this 20-hour sampling strategy, only rivalled by the regions of Monte Pascoal, in southern Bahia (Nemésio, 2013d), and Linhares, in northern Espírito Santo (Nemésio, 2013b).…”
Section: Sampling Protocolmentioning
confidence: 90%
See 1 more Smart Citation
“…Roubik (2004a) had already suggested that surveys of orchid-bee males with scent baits during a single day have great utility, and may reveal almost as much about local community structure as studies lasting a full year. The protocol proposed by Nemésio (2010b) has already been used in more than twenty areas in northeastern Brazil (Nemésio, 2010b; this study), southern Bahia (Nemésio, 2011a(Nemésio, , 2013a, northern Espírito Santo (Nemésio, 2011b(Nemésio, , 2013b, Minas Gerais (Nemésio, 2012c;Nemésio and Paula, 2013), and the Peruvian Amazon (Nemésio et al, 2014), always with a high number of collected specimens during a relatively short period of time. With more than 3,000 bees collected in only ten days, the present study revealed one of the highest abundances ever recorded with this 20-hour sampling strategy, only rivalled by the regions of Monte Pascoal, in southern Bahia (Nemésio, 2013d), and Linhares, in northern Espírito Santo (Nemésio, 2013b).…”
Section: Sampling Protocolmentioning
confidence: 90%
“…Roubik, 2004b;Oliveira, 2006;Rasmussen and Skov, 2006;Nemésio, 2006Nemésio, , 2007Nemésio, , 2008Nemésio, , 2009Nemésio, , 2010aNemésio, , 2011bNemésio, , c, d, 2012aAyala and Engel, 2008;Bembé, 2008;Hinojosa-Díaz and Engel, 2011a, b;Hinojosa-Díaz et al, 2011Nemésio and Engel, 2012), faunistic and ecological studies in the last decade have been mainly focused on the Atlantic Forest of eastern Brazil (e.g. Bezerra and Martins, 2001;Tonhasca Júnior et al, 2002;Santos and Sofia, 2002;Martins and Souza, 2005;MiletPinheiro and Schlindwein 2005;Darrault et al, 2006;Nemésio and Silveira, 2006b, 2007a, 2010Farias et al, 2007;Farias et al 2008;Aguiar andGaglianone, 2008, 2011;Moura and Schlindwein, 2009;Nemésio, 2010bNemésio, , 2011aNemésio, , b, e, 2012cMattozo et al, 2011;Cordeiro et al, 2013;Nemésio and Vasconcelos, 2013), although a few studies have also been conducted in the Amazon Morato, 2004, 2006;StorckTonon et al, 2009;Rasmussen, 2009;Abrahamczyk et al, 2011;Nemésio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although some uncommon species, such as Aglae caerulea Lepeletier and Serville, 1825, were attracted to trans-methyl cinnamate and although this species seems to present a strong preference for this scent (Morato, 2001;Nemésio et al, 2014), it is also attracted to eugenol (this study) and skatole (Nemésio et al, 2014). Important scents in the Amazon basin, such as benzyl acetate and skatole (Oliveira and Campos, 1996;Morato, 2004, 2006;Storck-Tonon et al, 2009;Nemésio et al, 2014), were not used in the present study, since these scents were not available to us prior to the field work. Nevertheless, most species attracted to these scents are also attracted to cineole, methyl-salicylate and vanillin (see Table 1 and Storck-Tonon et al (2009): 697).…”
Section: Scent Attractivenessmentioning
confidence: 99%
“…Synthetic aromatic scents that mimic the floral fragrances attractive to male orchid bees have been used since the late 1960's (Vogel, 1966;Dodson et al, 1969) as powerful tools in field studies involving these bees (e.g. Nemésio and Silveira, 2006, 2007, 2010Rasmussen, 2009;Abrahamczyk et al, 2011). These studies eventually led to the discovery of a previously unknown astonishing diversity among orchid bees (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation